The Academic Administration of Executives Affecting the Desired Characteristics of Vocational Graduates under the Nakhon Pathom Provincial Vocational Education Office - Khueanphet, Thanawat; Jinadattiyo, Phramaha Kraiwan (Journal of Dhamma for Life, 2025)
The purposes of this research were: 1) Study the academic administration of executives under the Nakhon Pathom Provincial Vocational Education Office. 2) Examine the desired characteristics of vocational graduates under the Nakhon Pathom Provincial Vocational Education Office, 3) Investigate the impact of academic administration on the desired characteristics of vocational graduates under the Nakhon Pathom Provincial Vocational Education Office. The sample group consisted of 11 school administrators, 11 deputy school administrators, and 20 department heads or teachers, totaling 242 respondents. The research instrument used was a questionnaire, and data were analyzed using statistical software. The statistical methods applied included Frequency, Percentage, Arithmetic Mean, Standard Deviation, and hypothesis testing using Stepwise Multiple Regression Analysis. The results of this research were as follows: 1) The academic administration of executives under the Nakhon Pathom Provincial Office of Vocational Education is generally at a high level. The ranking from highest to lowest is as follows: academic departments, curriculum development and instruction, assessment and evaluation, academic services and library, dual vocational education, and instructional media, respectively. 2) The desired characteristics of vocational graduates under the Nakhon Pathom Provincial Vocational Education Office were found to be at a high level overall. When ranked from highest to lowest, they included knowledge, morality and ethics, desired personal attributes, and skills and application, respectively. 3) The academic administration of executives that significantly affected the desired characteristics of vocational graduates under the Nakhon Pathom Provincial Vocational Education Office at a statistical significance level of .05 included, in order of importance, the dual vocational education system, instructional media, department-level management, and assessment and evaluation. The multiple correlation coefficient (Multiple R) was .894, indicating that these variables together predicted 80.0 percent (R2 = .800), which can be written as a regression analysis equation as follows. Forecast equations in raw score form tot = .121 + .038 (X1) + .045 (X3) + .048 (X5) + .052 (X6) (R2 = .800) Forecast equations in standard score form z = .151 (zx1) + .152 (zx3) + .333 (zx6) + .357 (zx5) (R2 = .800).